Florid cemento-osseous dysplasia and peripheral giant cell granuloma in a patient with neurofibromatosis 1 - Dmitry José de Santana Sarmento; Sérgio Henrique Gonçalves de Carvalho; José Cadmo Wanderley Peregrino de Araújo Filho; Marianne de Vasconcelos Carvalho; Éricka Janine Dantas da Silveira (Sociedade Brasileira de Dermatologia, 2017)
Abstract: We report a 35-year-old mulatto female patient with neurofibromatosis Type 1 who presented with facial asymmetry. The patient had two lesions: florid cemento-osseous dysplasia associated with peripheral giant cell granuloma. She was referred for surgical treatment of the peripheral giant cell granuloma and the florid cemento-osseous dysplasia was treated conservatively by a multidisciplinary team. So far, no changes have been observed in the patient's clinical status. We observed no recurrence of peripheral giant cell granuloma. To the best of our knowledge, the present case is the first report of a patient with neurofibromatosis Type 1 associated with a giant cell lesion and florid cemento-osseous dysplasia.